A regular ternary conjugated polymer bearing π-extended diketopyrrole and isoindigo acceptor units for field-effect transistors and photothermal conversion. (May 2019) - Du, Yuchang; Ding, Yafei; Ge, Feng; Wang, Xiaohong; Ma, Suxiang; Lu, Hongbo; Zhang, Guobing; Qiu, Longzhen
Abstract: A new π-extended electron-deficient unit, 6, 6′-(5, 5′-N, N'-(2-ethylhexyl)-isoindigo-6, 6′-diyl)bis(thiophene-5, 2-diyl))bis(2, 5-bis(2-decyltetradecyl)-3-(thiophen-2-yl)pyrrolo[3, 4-c]-pyrrole −1, 4 (2H, 5H)-dione) (2DPPI) was designed and synthesized. Three new D-A conjugated polymers were then synthesized based on 2DPPI unit and different electron-donors thiophene, thieno[3, 2-b]thiophene and 2, 2′-bithiophene. Their photophysical properties, electrochemical behaviors, field-effect characteristics, thin-films morphologies, and photothermal conversion performances were systematically investigated. All three polymers displayed broad and strong absorption in the near infrared region. Compared with the corresponding DPP-based polymers, the 2DPPI-based polymers possess deeper the highest occupied molecular orbital and the lowest unoccupied molecular orbital levels and narrower band gap due to the introduction of large acceptor formed by IID and DPP. The OTFT devices based on three polymers were fabricated, and their field-effect performance were characterized under ambient conditions. After annealing, P2DPP-BT showed the maximum hole mobility of 0.224 cm 2  V −1  s −1 and an electron mobility of 0.033 cm 2  V −1  s −1 . The corresponding microstructure and morphology analyses revealed that P2DPPI-BT showed more ordered molecular stacking, lamellar packing and well-interconnected larger domains, all of which are favorable to the carrier transport. In addition, the photothermal test reviews that all three polymer films can effectively convert near infrared light to heat, and P2DPPI-TT has the highest photothermal conversion efficiency of 25.6%. Furthermore, P2DPPI-TT was successfully used for tuning cholesteric liquid crystal reflective band under the irradiation of near infrared light. Graphical abstract: Image 1 Highlights: A new π-extended electron-deficient unit 2DPPI was designed and synthesized. Three polymers were synthesized and displayed broad and strong NIR absorption. The polymers showed excellent photothermal conversion efficiency (25.6%). A novel NIR-light modulated liquid crystal was achieved using the polymer. Polymers showed hole-dominated ambipolar characteristics under ambient conditions.